Cecal volvulus: a rare entity of acute bowel obstruction - Madrid Ruíz, José Francisco; Alonso López, Elsa Paulina; Hidalgo Artiaga, Karen Elena; Vargas Sahagún, César Manuel (International Journal of Research in Medical Sciences, 2022)
Cecal volvulus is characterized by an axial torsion of the cecum, terminal ileum and ascending colon, being the third cause of bowel obstruction with an incidence of 2%, considered a rare pathology. We presented a rare case of a patient with a bowel obstruction secondary to cecal volvulus found during exploratory laparotomy.